O efeito de vídeos de alimentação saudável sobre as escolhas de alimentos em crianças - SOUZA, Gilvandro Figueiredo (Universidade Federal do Pará, 2019)
Videos about of nutrition education, publicity, advertising and entertainment are widely used as a means of communication. Many of them are used to encourage the consumption of foods. However, most of the time, the videos that talk about such consumption, focus on the development of broad dissemination of high in fat, sodium and sugar foods, in excess, are harmful to health. All this disclosure just promoting an increase in the consumption of unhealthy foods and, consequently, reducing the practices of good nutrition education. Based on this fact the Study 1 was conducted to evaluate the effect of videos about healthy food choices healthy food for children. What was to present, through educational videos, the various types of foods consumed by man. As participants in this study among children aged between 10 and 11 years old that might among the various types of food make your own choice. Participated in Study I, 24 children between 10 and 11 years of age, of both sexes, regularly enrolled in elementary school. The study I was divided into three stages. In the Stage I the appointment of foods was assessed with appropriate phase correction. In the Stage II, children were exposed to pre - test selection of healthy and unhealthy foods, the videos of healthy foods, the assessment of understanding of test videos, and finally again to test food choices. In the Stage III consisted only in the testing of food after a week of intervention. The results indicate that the videos showed effect on most healthy choices for children. But, this effect was temporary. In Study II, a questionnaire was applied to verify the food preferences of children in the same study 1 and 164 other children of the same grade and age. The results indicate that there is a slight preference for unhealthy foods, but in general, preference is given at a ratio of 1/1. Studies investigating the control variables of feeding behavior are extremely important for preventing obesity, promoting healthy habits and discussion of public policy Nutritionally, Industrial, Commercial and Consumer Behavior.